Comparison of Vitamin-D binding protein levels in gingival crevicular fluid of pre- and postmenopausal women with and without chronic periodontitis: A clinico-biochemical study - Kaviya Balasubramaniyam; Sankar Lakshmi Sree; Kavitha Jayavel; V. Krishnan; Rajasekar Sundaram (SRM Journal of Research in Dental Sciences)
Background: Periodontitis is a multifactorial chronic inflammatory condition that affects the supporting tissues of the teeth, and menopause can contribute to its progression. Vitamin-D Binding Protein (DBP) is a multifunctional protein that acts as an acute phase reactant and plays a key role in bone metabolism. Aim: The aim of this study was to assess and compare DBP levels in Gingival Crevicular Fluid (GCF) of pre- and postmenopausal women with and without chronic periodontitis. Materials and Methods: Fifty-two female participants aged 35–60 were selected from outpatients’ clinics and divided into premenopausal and postmenopausal groups. Plaque index, gingival bleeding index, probing pocket depth, and clinical attachment level were measured. GCF DBP levels were evaluated using an enzyme-linked immunosorbent assay kit. Results: There was a significant correlation between menopausal status and periodontal status in relation to GCF DBP levels (P = 0.000). However, regardless of the menopausal status, participants with periodontitis exhibited a five-fold increase in mean GCF DBP levels compared to those without periodontitis. There was a significant positive correlation existed between the periodontal parameters and GCF DBP levels. Conclusion: Based on the findings, we conclude that GCF DBP is influenced more by participants’ periodontal health than by their menopausal status, and it correlates favorably with the degree of periodontal destruction.